An analysis of the funding gap in the human capital development matrix in Zimbabwe - Gurira, Candice (Midlands State University, 2017)
The study is an analysis of the funding gap in the human capital development matrix in Zimbabwe. The research was motivated by failure of Zimbabwe Manpower Development Fund to pay industrial attachment for university students and also to equip institutions of higher learning with modern equipment due to lack of funding. The objectives of the study were to establish the existence of the funding policy, assess the adequacy of the personnel to engage industry in debt collection Literature was reviewed from authoritative authors, which was related to the research topic. This research looked at the funding policies applied by other countries in the Sub-Saharan Africa such as Botswana, Tanzania, South Africa and Zambia. The researcher adopted the descriptive research design, and questionnaires and interviews were used as the main data collection instruments. Data was presented in tables and charts. Major research findings revealed that the major source of funding for ZIMDEF was not sufficient to meet the training needs of Zimbabwe. There is need for the Fund to augment it 1% training levy given the current economic situation in Zimbabwe. To bridge the funding gap, the Fund must consider donor funding for capital projects and acquisition of modern equipment, should also ensure that each department is housed with relevant people